Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1973
DOI: 10.1139/m73-014
|View full text |Cite
|
Sign up to set email alerts
|

On the mycophage of Penicillium chrysogenum

Abstract: A mycovirus has been purified from mycelia of Penicillium chrysogenum by isopycnic centrifugation in sucrose and in CsCl. Viral particles band with a buoyant density of 1.20 in sucrose and 1.38 in CsCl. Particles have icosohedral symmetry, are 35 nm in diameter, and have an absorption profile characteristic of nucleoprotein. One enzymatic activity, RNA polymerase, is associated with the purified mycophage. Nucleic acid extracted from purified virus has a buoyant density in CS2SO4 of 1.61, a molar extinction co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

1973
1973
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 4 publications
3
37
0
Order By: Relevance
“…The PsV-F activity differs from that of Penicillium chrysogenum virus (Nash et aL 1973) in being dithiothreitol-independent and in its failure to be stimulated by Triton X-Ioo. The radioactive RNA synthesized in our reaction mixtures is not released from the virus particles, and most of it is double-stranded and, for PsV-F, coelectrophoreses with the various RNA species extracted from purified virus.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The PsV-F activity differs from that of Penicillium chrysogenum virus (Nash et aL 1973) in being dithiothreitol-independent and in its failure to be stimulated by Triton X-Ioo. The radioactive RNA synthesized in our reaction mixtures is not released from the virus particles, and most of it is double-stranded and, for PsV-F, coelectrophoreses with the various RNA species extracted from purified virus.…”
Section: Discussionmentioning
confidence: 70%
“…Viruses have been isolated from a wide range of fungi, and all of those studied in detail have turned out to consist of several density components and to contain several species of double-stranded RNA (Wood, 1973)-In the two published cases where it has been sought, evidence of a fungal virus-associated RNA-dependent RNA polymerase has been found; Nash et al (1973) reported a Mg ++-, dithiothreitol-and KCl-dependent RNA polymerase activity associated with Penicillium chrysogenum virus, and Lapierre, Astier-Manifacier & Cornuet (197I) described a Mg++-dependent, ethidium bromide-sensitive activity in P. stoloniferum virus (PsV); the product of this polymerase was partially resistant to pancreatic ribonuclease action.…”
Section: Introductionmentioning
confidence: 99%
“…Three classes of ds-RNA are also suggested from the data of Buck et al (43), Nash et al (45), and Cox et al (47,48 (23,43,45).…”
Section: Biophysical Properies Of Mycovirusesmentioning
confidence: 88%
“…Others have reported a particle diameter of 35 nm (42,43,45). A molecular weight of 13 x 106 daltons was computed from sedimentation and diffusion data (23).…”
Section: Biophysical Properies Of Mycovirusesmentioning
confidence: 99%
“…Virions associated with the fungus, Penicillium chrysogenum, contain dsRNA (8,9). The potent inhibitory activity of this dsRNA, used in all our experiments, is illustrated in Fig.…”
Section: If-3 Maintainsmentioning
confidence: 99%